Los actores sociales costarricenses frente al tratado de libre comercio Costa Rica / México inserción internacional y grado de preparación del país - Villalobos Céspedes, Daniel (Editorial Universidad Nacional (EUNA), 2002)
This research analyzes the political-technical capacity and the degree of knowledge of the social actors of the country, to formulate a strategy around a type of advantageous international insertion, adapted to the objectives of greater national socioeconomic well-being.